Answer:
[tex]d=\sqrt{m^{2}+n^{2} }[/tex]
Step-by-step explanation:
To find the distance between two points, we use the distance formula
[tex]d=\sqrt{((x_{2}-x_{1})^{2}+(y_{2}-y_{1})^{2} }[/tex].
Chose a point to be [tex](x_1,y_1)[/tex] and another point to be [tex](x_2,y_2)[/tex].
Let (0,n) be [tex](x_1,y_1)[/tex] where [tex]x_1=0\\y_1=n[/tex].
Let (m,0) be [tex](x_1,y_1)[/tex] where [tex]x_2=m\\y_2=0[/tex].
Substitute the values.
[tex]d=\sqrt{((m-0)^{2}+(0-n)^{2} }\\d=\sqrt{((m)^{2}+(-n)^{2} }\\d=\sqrt{m^{2}+n^{2} }[/tex]